A Reexamination of Diversification Premiums: An Information Asymmetry Perspective1. (April 2014) - Chae, Joon; Jung, Jin‐Young; Yang, Cheol‐Won
Abstract Acquiring firms that earn positive abnormal returns on acquisitions may have internal capital markets that overcome the information asymmetry costs in less‐developed capital markets. In this paper, through an examination of data on 1064 acquiring firms in the Korean market from 1994 to 2011, we find that the highest acquiring returns occur when the firms with high information asymmetry acquire firms with low information asymmetry. To measure the degree of information asymmetry, we use the models of Glosten–Harris (1988), Hasbrouck (1991) and Foster–Viswanathan (1993), which we selected from a variety of studies on market microstructure. We also find that the effect of information asymmetry on mergers and acquisitions (M&As) was larger before the Asian financial crisis of 1998, as well as before the global financial crisis of 2007, and that the Korean capital market was less developed before these crises than after them. We show that the internal capital market hypothesis holds for M&As, and that information asymmetry is a strong determinant of M&A decisions in emerging markets.